Does Maternal Education Affect Childhood Immunization Rates? Evidence from Turkey - Mustafa Özer; Jan Fidrmuc; Mehmet Ali Eryurt (Center for Economic Studies and ifo Institute (CESifo), 2017)
We study the causal effect of maternal education on childhood immunization rates. We use the Compulsory Education Law (CEL) of 1997, and the differentiation in its implementation across regions, as instruments for schooling of young mothers in Turkey. The CEL increased the compulsory years of schooling of those born after 1986 from 5 to 8 years. We find that education of mothers increases the probability of completing the full course of DPT and Hepatitis B vaccinations for their children. Furthermore, education increases the age of first marriage and birth, changes women`s and their spouse's labour market status, and significantly affects women`s attitude towards spousal violence against women and gender discrimination in a manner that empowers women.
Keywords: H51; H52; I12; 330; DPT (diphtheria; pertussis and tetanus); Hepatitis B; maternal education; autonomy of women; fertility; difference-in-difference-in-differences; instrumental variable